Analisis Buku Metode Asy-Syafi'i sebagai Bahan Ajar Tajwid pada Santri Usia SD di Rumah Qur'an Qurrota A'yun - Ida Ruhaeni; Anie Rohaeni (Jurnal Pendidikan Educandum, 2026)
This study aims to identify and analyze the Asy-Syafi'i Method book as a tajwid teaching material based on its implementation in halaqah for elementary school-aged santri at Rumah Qur'an Qurrota A'yun (RQQA). The scope of analysis was limited to the material that had been taught, namely Iqra enrichment starting from recognizing the reading of Al in the first lesson to recognizing waqf signs in the fifth lesson. This research focuses on the book's feasibility in the context of real implementation at RQQA, with the discussion directed at field findings based on three aspects: the suitability of the book's content with student characteristics, the language aspect, and the presentation aspect. This study employed a qualitative approach with a field research design, using observation, interview, and documentation techniques involving the coordinator, two teachers, and four santri. The results show that the book is conditionally feasible for elementary school-aged santri at RQQA. The content suitability was not optimal for third-grade students who required intensive guidance, the language used required simplification by teachers, and the presentation aspect — particularly the black-and-white graphics — was less motivating for santri. It is concluded that the book can be used with the note that teachers must actively serve as mediators and that the addition of color elements is necessary. This finding is expected to serve as a consideration for developers of children's tajwid books in improving the quality of teaching materials, as well as a reference for other Qur'an houses in selecting and using tajwid books that are appropriate for elementary school-aged students.